Qualitative analysis of cardiovascular disease prevention in dental practice - Áine O'Farrell; Chee H. Liew; Rosemary Geoghegan; Gerard T. Flaherty (Public Health in Practice)
Background: The primary prevention of periodontal disease is a global health concern due to its increasing incidence and evolving evidence of its role in cardiovascular disease (CVD). This study aimed to describe dentists’ perceptions and practices regarding CVD prevention in practice. Study design and methods: A qualitative study design, using semi-structured interviews, was used to determine the perceptions, practices, barriers, and enablers of dentists towards the implementation of CVD prevention in practice. Interviews were analysed using a thematic analysis framework. NVivo 12 Pro software was utilised to support the data analysis. Results: Eleven participants (eight female) with a mean employment history of 17.45 years, were interviewed, at which point data saturation was reached. The semi-structured interviews ranged in duration from 45 to 86 min, with a mean duration of 62.5 min. All dentists interviewed were in private practice. Inductive thematic analysis revealed four major themes - dentists’ current practices in relation to preventive cardiology in practice; professional identity and role expectations; barriers to preventive cardiology in practice; and facilitators of preventive cardiology in dental practice. Conclusions: This study highlights the current practices, perceptions and identified barriers and enablers to preventive cardiology in Irish dental practice. Future research should focus on educational interventions to improve the implementation of CVD prevention guidelines in dental practice.